Predictive Validity of the Patient Health Questionnaire‐9 for Depression in Poststroke Patients: A Systematic Review and Meta‐Analysis - Junya Chen; Mei Chan Chong; Hmwe Nant Thin Thin; Fen Xu; Xiao Dong; Xiaoxian Yang; Ruan Jia Yin; Huimin Hong (Brain and Behavior)
ABSTRACT Background The Patient Health Questionnaire‐9 (PHQ‐9), known for its brevity and ease of use, is employed by researchers and clinical practitioners for poststroke depression (PSD) screening. However, the effectiveness of the PHQ‐9 in PSD screening remains to be further validated. Methods Electronic searches were conducted in EMBASE, PubMed, Web of Science, CNKI, and Wanfang databases using keywords including stroke, depression, and PHQ‐9. The assessment tool Quality Assessment of Diagnostic Accuracy Studies‐2 was utilized to evaluate the risk of bias in diagnostic studies. Results A total of 2049 articles were retrieved, with 9 meeting the inclusion criteria. The PHQ‐9 demonstrated pooled sensitivity and specificity of 0.84 and 0.90, respectively, and a summary receiver operating characteristic (sROC) curve of 0.93. At the 10‐cut‐off value, pooled sensitivity, specificity, and sROC were 0.77, 0.85, and 0.86, respectively. At the 9‐cut‐off value, the sensitivity, specificity, and sROC were 0.87, 0.85, and 0.92, respectively. At the 5‐cut‐off value, sensitivity, specificity, and sROC are 0.90, 0.91, and 0.96, respectively. No publication bias was identified. Conclusion The PHQ‐9 is an effective tool for screening poststroke depressive symptoms with significant clinical utility. However, further research is needed to establish optimal diagnostic thresholds.